Household consumption function based on permanent income hypothesis: A systematic review - Wong, Sing Yun; Siti Hajar Samsu; Jain Yassin; Shairil Izwan Taasim; Faerozh Madli (Human Resource Management Academic Research Society, 2023)
The Permanent Income Hypothesis was first proposed by Milton Friedman in the 1950s and has been an important theory in the field of macroeconomics. According to this theory, the spending behavior of individuals is based on their long-term average income rather than their current income. The theory posits that individuals adjust their spending patterns based on their expected lifetime income rather than temporary fluctuations in their income. Given the severe impact of COVID-19 on household consumption and income change, it becomes increasingly important to model household consumption. With this subject becoming increasingly significant, it is noteworthy to retrieve and report on the existing literature, especially within the context of explaining the Permanent Income Hypothesis (PIH) relevancy to model household consumption. This study will employ the PRISMA strategy in the systematic review of the existing literature. The finding from this review showed the literature found can be clustered into three (3) themes in answering the research questions and contributing to the existing body of knowledge in this domain. Finally, this systematic review will advance the literature and provide recommendations for policy formulation, as well as paving way for future studies within this context.